The diagnostic and immunomodulatory role of IL-37 in pediatric sepsis - Ma, Jin; Zhang, Yanling; Sun, Changrui; Yang, Hao; Song, Zhixin; Huang, Feiqi; Wu, Chunxiang (Frontiers in Immunology, 2026)
ObjectiveSepsis arises from a dysregulated host inflammatory response to infection. The levels and pathogenic role of interleukin-37 (IL-37) in pediatric sepsis remain to be fully elucidated.MethodsSerum IL-37 concentrations were measured in two independent cohorts of pediatric patients with sepsis from Chongqing (discovery cohort, n=40) and Sichuan (validation cohort, n=105). The immunomodulatory effects of IL-37 were systematically investigated through: 1) a murine sepsis model (cecal ligation and puncture), and 2) ex vivo experiments using peripheral blood mononuclear cells (PBMCs) from patients under standardized culture conditions.ResultsAdmission serum IL-37 levels were significantly higher in pediatric patients with sepsis compared to non-septic patients and healthy controls. To assess its diagnostic potential, ROC curve analyses were performed, yielding areas under the curve (AUC) of 0.76 [P<0.0001; 95% confidence interval (95% CI), 0.66 - 0.85] and 0.77 [P<0.0001; 95% CI, 0.71 - 0.84] from the two medical centers. In septic mice, therapeutic administration of recombinant IL-37 significantly attenuated systemic inflammation (reduced IL-6, CXCL-1, CCL-2; increased IL-10), decreased the proportion of M1 macrophages without altering total macrophage counts in peritoneal lavage fluids (PLF), and improved survival rates. In vitro, IL-37 neutralization with a specific antibody in septic PBMCs increased the percentages of CD4+ T cells and NKT cells.ConclusionThis study identifies elevated IL-37 as a potential diagnostic biomarker for pediatric sepsis and demonstrates its role in modulating hyperinflammation and immune cell differentiation. IL-37 represents a promising therapeutic target for pediatric sepsis.